Ministerial decree no. 846/2017 promulgating the executive regulations of law no. 121/1982 concerning the importers register = قرار وزاري رقم 846 لسنة 2017 بإصدار اللائحة التنفيذية للقانون رقم 121 لسنة 1982 في شأن سجل المستوردين - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of trade and industry decree no. 846 of the year 2017 promulgating of law no. 121 of the year 1982 concerning the imports register وزارة التجارة والصناعة قرار رقم 846 لسنة 2017 باللائحة التنفيذية للقانون رقم 121 لسنة 1982 فى شأن سجل المستوردين